Introduction to econometrics : principles and applications - Kelejian, Harry H.; Oates, Wallace E. (New York : Harper & Row, 1974)
The book is meant to serve as a text for a one-semester course in econometrics at either the undergraduate or masters level. Masters level means those students who do not have either the mathematical or statistical training to work through more advanced formal presentations of econometrics.The pre-requisites for this text is roughly the first two-thirds of a one-semester course in elementary statistics.
Includes index.
Includes bibliographical references: p. 269.
rpm 25/09/2017
Loans
Keywords: Econometrics